INCREASING OF EFFICIENCY OF THE SEWAGE WATERS CLEARANCE IN THE SYSTEMS OF WATER RECYCLING OF CASTING HOUSES - Ju. P. Ledjan (Литьë и металлургия)
The new technological process and equipment for dissolution of the high-molecular flocculants, increasing efficiency of the wastewaters clearing, is developed